Political reorientation of Japan, September 1945 to September 1948 : (Scholarly Press, 1949)
This report on the political reorientation of Japan during the first 3 years of the Allied occupation of that country was prepared in the Government Section of General Headquarters, Supreme Commander for the Allied Powers.